2017
DOI: 10.1037/ser0000156
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice as a potential solution to burnout in university counseling center clinicians.

Abstract: The purpose of this study was to evaluate the impact of changes in perceptions about patient volume and severity of clinical presentations in university counseling centers (UCCS) on burnout. It was hypothesized that perceptions of increased workload and severity of conditions treated would be positively correlated with burnout. It was also hypothesized that self-reported use of evidence-based practice (EBP) would be negatively correlated with burnout. Counseling center clinicians (n = 80) completed the Copenha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Burnout was less common among therapists who had been counseling longer and those who perceived their management to be more supportive (Sodeke-Gregson et al 2013 ). Furthermore, Wilkinson et al ( 2017 ) found that among mental health professionals in American college counseling centers, 19% scored above the cutoff for personal burnout, 15.2% for work burnout, and 2.5% for client burnout. Counselors’ perceptions that clients’ presenting concerns were increasing in severity significantly, positively correlated with all three types of burnout (Wilkinson et al 2017 ).…”
Section: Counseling Traumatized Clients and Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Burnout was less common among therapists who had been counseling longer and those who perceived their management to be more supportive (Sodeke-Gregson et al 2013 ). Furthermore, Wilkinson et al ( 2017 ) found that among mental health professionals in American college counseling centers, 19% scored above the cutoff for personal burnout, 15.2% for work burnout, and 2.5% for client burnout. Counselors’ perceptions that clients’ presenting concerns were increasing in severity significantly, positively correlated with all three types of burnout (Wilkinson et al 2017 ).…”
Section: Counseling Traumatized Clients and Burnoutmentioning
confidence: 99%
“…Furthermore, Wilkinson et al ( 2017 ) found that among mental health professionals in American college counseling centers, 19% scored above the cutoff for personal burnout, 15.2% for work burnout, and 2.5% for client burnout. Counselors’ perceptions that clients’ presenting concerns were increasing in severity significantly, positively correlated with all three types of burnout (Wilkinson et al 2017 ). In contrast, Garcia et al ( 2016 ) investigated burnout among 137 clinicians in the United States who provided prolonged exposure or cognitive processing therapy for veterans.…”
Section: Counseling Traumatized Clients and Burnoutmentioning
confidence: 99%
“…Although CPT offered a time-limited, empirically supported option for staff, the treatment has not been widely implemented in UCCs. Wilkinson et al (2017) surveyed UCC therapists and only 1.8% of therapists surveyed endorsed using CPT to treat college students diagnosed with PTSD. Slightly more (5.5%) endorsed use of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Wilkinson et al . (2017) surveyed UCC therapists and only 1.8% of therapists surveyed endorsed using CPT to treat college students diagnosed with PTSD. Slightly more (5.5%) endorsed use of PE.…”
Section: Introductionmentioning
confidence: 99%
“…This effectively leaves trainers in evidencebased protocols with starting to disseminate the treatment all over again in these front-line settings, and then the cycle repeats after a new cohort of providers have been trained. It is interesting to note that some studies have shown that community practitioners who more regularly engage in the use of evidence-based treatments report less burnout when dealing with complex cases (e.g., as found in university counseling centers; Wilkinson, Infantolino, & Wacha-Montes, 2017), which may be an important finding to encourage use of evidencebased protocols in community mental health clinics. Another problem in implementation is that the trained providers may not have the time in their current settings where such training is offered to actually implement protocol treatment, and are more likely to abandon such practices when they move to a new setting or when the expert supervision/other training resources are reduced, reverting to old, non-EST practices that are more familiar (McLean & Foa, 2013;Parks, 2007).…”
Section: High Turnover Of Providersmentioning
confidence: 99%